Photogeneration of two reduction-active charge-separated states in a hybrid crystal of polyoxometalates and naphthalene diimides. Issue 2 (24th November 2014) - Liu, Jian-Jun; Wang, Yao; Lin, Mei-Jin; Huang, Chang-Cang; Dai, Wen-Xin
Abstract : Upon irradiation, two kinds of long-lived charge-separated states for the reduction reactions can be generated in a hybrid crystal composed of two-dimensional naphthalene diimide coordination networks and polyoxometalates. Abstract : The combination of naphthalene diimide tectons with zinc cations in the presence of polyanions, Mo6 O19 2−, leads to a hybrid crystal composed of two-dimensional porous coordination networks and polyoxometalates, which can generate two kinds of long-lived charge-separated states for the reduction reactions upon irradiation.